Mechanism‐Guided Design of Highly Efficient Protein Secretion and Lipid Conversion for Biomanufacturing and Biorefining. Issue 13 (1st May 2019) - Xie, Shangxian; Sun, Su; Lin, Furong; Li, Muzi; Pu, Yunqiao; Cheng, Yanbing; Xu, Bing; Liu, Zhihua; da Costa Sousa, Leonardo; Dale, Bruce E.; Ragauskas, Arthur J.; Dai, Susie Y.; et al.
Abstract: Bacterial protein secretion represents a significant challenge in biotechnology, which is essential for the cost‐effective production of therapeutics, enzymes, and other functional proteins. Here, it is demonstrated that proteomics‐guided engineering of transcription, translation, secretion, and folding of ligninolytic laccase balances the process, minimizes the toxicity, and enables efficient heterologous secretion with a total protein yield of 13.7 g L −1 . The secretory laccase complements the biochemical limits on lignin depolymerization well in Rhodococcus opacus PD630. Further proteomics analysis reveals the mechanisms for the oleaginous phenotype of R. opacus PD630, where a distinct multiunit fatty acid synthase I drives the carbon partition to storage lipid. The discovery guides the design of efficient lipid conversion from lignin and carbohydrate. The proteomics‐guided integration of laccase‐secretion and lipid production modules enables a high titer in converting lignin‐enriched biorefinery waste to lipid. The fundamental mechanisms, engineering components, and design principle can empower transformative platforms for biomanufacturing and biorefining. Abstract : Proteomics‐based systems biology reveals the molecular mechanisms of protein secretion, lignin catabolism, and lipid biosynthesis in Gram‐positive bacteria Rhodococcus opacus PD630. The mechanism‐guided biodesign of a R. opacus PD630 system achieves direct lignin bioconversion to high lipid yield by creating a highly efficient laccase heterologous secretion system and integrating an optimized lipid biosynthesis pathway.